2006
DOI: 10.1897/05-321r.1
|View full text |Cite
|
Sign up to set email alerts
|

Effect of simulated rhizodeposition on the relative abundance of polynuclear aromatic hydrocarbon catabolic genes in a contaminated soil

Abstract: Microcosms were used to investigate whether soil exposure to mulberry root extracts (rich in phenolic compounds) select for bacteria that degrade polynuclear aromatic hydrocarbons (PAHs). Unlike previous studies with freshly spiked soil, the present experiments were conducted with soils aged for 518 d with [14C]phenanthrene to decrease bioavailability and avoid exaggerating the selective pressure exerted by PAHs relative to the rhizosphere effect. Microcosms simulating contaminated planted soil were exposed to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 33 publications
0
22
1
Order By: Relevance
“…Although in our study cumulative mineralization of both hexadecane and naphthalene in most treatments reached parity after 28 days (Table 1), the initial and variable repressive effects offer insights into the underlying mechanisms of plant-microbe interactions in these systems. Previous studies have linked increased hydrocarbon degradation in exudate amended systems to non-specific increases in bacterial populations (Da Silva et al, 2006;Kamath et al, 2004;Rentz et al, 2004;Tuomi et al, 2004). In this study however, DGGE analysis revealed no detectable difference in the type or relative abundance of the dominant bacterial species found in the different treatments (Fig.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…Although in our study cumulative mineralization of both hexadecane and naphthalene in most treatments reached parity after 28 days (Table 1), the initial and variable repressive effects offer insights into the underlying mechanisms of plant-microbe interactions in these systems. Previous studies have linked increased hydrocarbon degradation in exudate amended systems to non-specific increases in bacterial populations (Da Silva et al, 2006;Kamath et al, 2004;Rentz et al, 2004;Tuomi et al, 2004). In this study however, DGGE analysis revealed no detectable difference in the type or relative abundance of the dominant bacterial species found in the different treatments (Fig.…”
Section: Discussioncontrasting
confidence: 56%
“…Artificial root exudates have been shown to increase bacterial densities, shift metabolic profiles (Baudoin et al, 2003), and stimulate hydrocarbon degrader populations (Joner et al, 2002). Similarly, root extracts and exudates have been shown to stimulate both general (Da Silva et al, 2006;Miya and Firestone, 2001) and group-specific (Yoshitomi and Shann, 2001) increases in PAH degrader populations. Other studies however, have implicated exudates in the repression of hydrocarbon degradation potential.…”
Section: Introductionmentioning
confidence: 99%
“…In our study, alders were able to promote microbial activity without the addition of any fertilizer. It was demonstrated that rhizodeposition (root turnover and plant exudates) can increase the relative abundance of genes involved in PAH degradation (Da Silva et al, 2006). In this study, microbial enumeration of total heterotrophs and PAH-degrading bacteria clearly showed that rhizosphere soil sustained a higher population density of microorganisms than bulk soil.…”
Section: Discussionmentioning
confidence: 59%
“…In this review, we clearly identified root exudates as a key ecological driver in the rhizosphere. Although numerous studies speculated that root exudation of organic compounds is the driving factor behind hydrocarbon rhizoremediation [54,67,104,141,[227][228][229][230][231][232], the extent to which biodegradation is achieved is highly variable amongst plant species [54]. Furthermore, studies directly linking the composition and quantity of root exudates to hydrocarbon biodegradation are scarce [54].…”
Section: Discussionmentioning
confidence: 99%
“…Root exudation is now considered to be the most important factor in the mediation of hydrocarbon biodegradation in the rhizosphere [54, 67,104,141,[227][228][229][230][231][232]. Root exudates serve as a carbon source and energy for microorganisms, and also improve the hydrocarbon degradation in the rhizosphere by stimulating hydrocarbon-degrader populations [67].…”
Section: Impact Of Root Exudates On Hydrocarbon Degradationmentioning
confidence: 99%